High voltage vacuum-processed perovskite solar cells with organic semiconducting interlayers. Issue 11 (12th February 2020) - Babaei, Azin; Dreessen, Chris; Sessolo, Michele; Bolink, Henk J.
Abstract : The effect of n-type interlayers and electrodes on the voltage and stability of fully vacuum-deposited perovskite solar cells is evaluated. Abstract : In perovskite solar cells, the choice of appropriate transport layers and electrodes is of great importance to guarantee efficient charge transport and collection, minimizing recombination losses. The possibility to sequentially process multiple layers by vacuum methods offers a tool to explore the effects of different materials and their combinations on the performance of optoelectronic devices. In this work, the effect of introducing interlayers and altering the electrode work function has been evaluated in fully vacuum-deposited perovskite solar cells. We compared the performance of solar cells employing common electron buffer layers such as bathocuproine (BCP), with other injection materials used in organic light-emitting diodes, such as lithium quinolate (Liq), as well as their combination. Additionally, high voltage solar cells were obtained using low work function metal electrodes, although with compromised stability. Solar cells with enhanced photovoltage and stability under continuous operation were obtained using BCP and BCP/Liq interlayers, resulting in an efficiency of approximately 19%, which is remarkable for simple methylammonium lead iodide absorbers.